European yield model exponential decay constact modification for glulam after fire exposure - Shakimon, Mohd Nizam; Hassan, Rohana; Abd Malek, Nor Jihan; Zainal, Azman; Awaludin, Ali; Abdul Hamid, Nor Hayati; Lum, Wei Chen; Salit, Mohd Sapuan (Multidisciplinary Digital Publishing Institute, 2022)
Many real-scale fire tests have been performed on timber connections to analyze the mechanical behavior of timber connections in previous years. However, little research focused on the bending performance of glued laminated (glulam) timber beam bolted connections after fire exposure. In this paper, the three-dimensional numerical model of the glulam timber beam bolted connections was developed and validated by experimental results. The model can simulate temperature evolution in the connections and their mechanical behavior. In the real-scale test, three (3) samples were prepared for a four-point bending test at normal temperature, while another three (3) samples were tested after exposure to a 30-min standard fire and cooled down to normal temperature. The results show the reduction of the load-carrying capacity before and after exposure to the standard fire by 23.9 kN (71.8%), 8.3 kN (26.1%), and 20.2 kN (47.6%) for bolt diameters of 12 mm, 16 mm, and 20 mm, respectively. The numerical model aims to conduct a parametric study and propose the modification of the exponential decay constant, k, for tropical glulam timber to predict the load-carrying capacity of the glulam timber beam bolted connections after exposure to standard fire.